THE EFFECT OF FINANCIAL INDEPENDENCE ON ECONOMIC GROWTH OF THE GERBANGKERTASUSILA REGION - Risa Aulia Ramadhani; Zidna Fitriyana (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2019)
This study aims to determine the effect of financial independence on economic growth in the Gerbangkertasusila area (Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo, Lamongan), East Java. Regional financial independence is measured using the ratio of regional original income and the ratio of balancing funds to total regional income. This study uses panel data types with Random Effect models and time series data with the research period from 2010-2017. The results show that in the panel data model, local revenue (PAD) has a significant positive effect on economic growth. PAD reflects the source of income from the area so that when PAD has a positive effect on economic growth, it means that the higher regional financial independence will affect higher economic growth. Then, in the time series data model, it was found that there were five districts/cities with a positive and significant effect on local revenue, namely Bangkalan Regency, Mojokerto Regency and City, Surabaya City, and Sidoarjo Regency. On the other hand, there are four district/city balancing funds that have a signifi cant effect, namely Bangkalan Regency, Mojokerto Regency, Surabaya City, and Lamongan Regency